Perancangan Sistem Point of Sale Berbasis Web pada Warung Mie Ayam Pak Fit dengan Metode Waterfall - Dimastrio Darma Putra; Ferdi Yusri; Iqbal Husaini (CV. Shofanah Media Berkah, 2025)
Warung Mie Ayam Pak Fit is a micro scale culinary business that still relies on manual sales and financial record keeping, which may lead to data inaccuracies, loss of transaction information, and difficulties in preparing financial reports. This study aims to design a web based Point of Sales (POS) sales information system that can support a more organized sales transaction management process. The research method used is a descriotive qualitative approach with data collection techniques including observation, interviews, and literature review. The system design is developed using the Laravel framework with the Waterfall development method, which is limited to the system design stage only. The design stages include user requirements analysis, system modeling using Unified Modeling Language (UML), database design through Entity Relationship Diagram (ERD), and application user interface design. The results of this study are in the form of a sales information system design that is expected to serve as a reference for the development and implementation of a web based POS system to improve the accuracy of financial records and support business decision making at Warung Mie Ayam Pak Fit.